Not simply volcanoes – The Geoheritage of the Cretaceous System in the Land of the Extinct Volcanoes Geopark, West Sudetes (SW Poland) - Migoń, Piotr; Pijet-Migoń, Edyta (Geotourism/Geoturystyka, 2021)
Volcanic geoheritage is emphasized as the main asset and distinctive characteristic of the Land of Extinct Volcanoes Geopark in the West Sudetes (SW Poland). However, the geoheritage values of the region are not limited to the legacy of ancient volcanism but include various other elements. This paper explores the contribution of geosites that expose sedimentary rocks of Cretaceous age and landforms developed upon these rocks. Six localities from the Geopark area, included in the comprehensive regional inventory of geosites, are presented. They represent natural and man-made sandstone outcrops and show, among others, lithological variations, small- and large-scale post-sedimentary deformation structures, landforms arising from differential weathering (rock shelters, honeycombs), boulder fields and a sandstone xenolith in volcanic rocks. Next, five localities from outside the Geopark, but still within the Pogórze Kaczawskie region, are described. Qualitative and quantitative evaluation of both groups is attempted, and the results show that, in general, geosites within the Geopark rank higher. However at least two from the other group also have significant geotourist potential. Finally, a brief comparative analysis with other parts of the Sudetes, where Cretaceous sedimentary rocks occur, is offered.